Patient and partner dispositional optimism as a long-term predictor of illness representations in autoimmune diseases. (November 2017) - Karademas, Evangelos C; Ktistaki, Georgia; Dimitraki, Georgia; Papastefanakis, Emmanouil; Mastorodemos, Vasileios; Repa, Argyro; Gergianaki, Irini; Bertsias, George; Sidiropoulos, Prodromos; Simos, Panagiotis
We examined whether the dispositional optimism of patients suffering from an autoimmune disease as well as of their partners can predict, at a dyadic level, their representations of illness consequences, and personal and treatment control, assessed 1 year later. Patient optimism predicted several patient and partner illness representations. Partner optimism was unrelated to own or patient illness representations. Results highlight the strong long-term predictive power of patient optimism and underline the importance of the interpersonal function of personality traits. At the same time, study findings indicate that the dyadic effects of optimism are complex and probably conditional on several factors.